Unjuk kerja mesin diesel berbahan bakar biodiesel campuran jatropha – sawit 4 : 1 - Wahyudi, W.; Nadjib, M.; Mahottama, S.M. (Universitas Mataram, 2024)
The increasing need for energy and environmental problems caused by the use of fossil fuels make the development of alternative fuels very important. This research aims to explore the potential of a jatropha-palm biodiesel combination with a 4:1 composition as an alternative fuel. The methods employed include esterification and transesterification of both oils, along with physical property testing and diesel engine performance. Results indicate an increase in density and viscosity with increasing biodiesel concentration, while the calorific value decreases. The fuel injection angle also changes with a higher biodiesel proportion. The diesel engine exhibits variations in rotational speed and power depending on the load and type of fuel. Specific Fuel Consumption (SFC) increases with engine load. In conclusion, the jatropha-palm biodiesel combination holds potential as an alternative diesel engine fuel.